Uremia increases QRS duration after β‐adrenergic stimulation in mice. Issue 13 (8th July 2018) - Thomsen, Morten B.; Nielsen, Morten S.; Aarup, Annemarie; Bisgaard, Line S.; Pedersen, Tanja X.
Abstract: Chronic kidney disease (CKD) and uremia increase the risk of heart disease and sudden cardiac death. Coronary artery disease can only partly account for this. The remaining mechanistic links between CKD and sudden death are elusive, but may involve cardiac arrhythmias. For the present study, we hypothesized that a thorough electrophysiological study in mice with CKD would provide us valuable information that could aid in the identification of additional underlying causes of sudden cardiac death in patients with kidney disease. Partial (5/6) nephrectomy (NX) in mice induced mild CKD: plasma urea in NX was 24 ± 1 mmol/L ( n  = 23) versus 12 ± 1 mmol/L ( n  = 22) in sham‐operated control mice ( P  < 0.05). Echocardiography did not identify structural or mechanical remodeling in NX mice. Baseline ECG parameters were comparable in conscious NX and control mice; however, the normal 24‐h diurnal rhythm in QRS duration was lost in NX mice. Moreover, β ‐adrenergic stimulation (isoprenaline, 200  μ g/kg intraperitoneally) prolonged QRS duration in conscious NX mice (from 12 ± 1 to 15 ± 2 msec, P  < 0.05), but not in sham‐operated controls (from 13 ± 1 to 13 ± 2 msec, P  >   0.05). No spontaneous arrhythmias were observed in conscious NX mice, and intracardiac pacing in anesthetized mice showed a comparable arrhythmia vulnerability in NX and sham‐operated mice. Isoprenaline (2 mg/kg intraperitoneally) changed the duration of the QRS complex from 11.2 ± 0.4 to 11.9 ± 0.5 ( P  = 0.06) in NX mice and from 10.7 ± 0.6 to 10.6 ± 0.6 ( P  = 0.50) in sham‐operated mice. Ex vivo measurements of cardiac ventricular conduction velocity were comparable in NX and sham mice. Transcriptional activity of Scn5a, Gja1 and several profibrotic genes was similar in NX and sham mice. We conclude that proper kidney function is necessary to maintain diurnal variation in QRS duration and that sympathetic regulation of the QRS duration is altered in kidney disease. Abstract : Chronic kidney disease (CKD) and uremia increase the risk of heart disease and sudden cardiac death, potentially caused by arrhythmias. We studied cardiac electrophysiology in a mouse model for CKD. We find that proper kidney function is necessary to maintain diurnal variation in QRS duration and that sympathetic regulation of the QRS duration is altered in kidney disease.